Incorporation of a theme‐based research model into a pharmacy department research program. (29th May 2019) - Welch, Susan; Johns, Rachelle; Nicholls, Gary; Bennett, Glenn; Kettle, Emily; Duong, Minh‐Tu; Finckh, Andrew; Berry, Melinda; Woods, Nikki; Branch, Judy; Tong, Winnie; Duffy, Martin
Abstract: In Australian hospital pharmacy departments, research programs are growing. Research is encouraged to be part of standard practice by many Society of Hospital Pharmacists of Australia (SHPA) Standards of Practice documents and, in 2017, the SHPA National Translational Research Collaborative was implemented. Traditionally, the postgraduate research degree format is one of a theme‐based research model. Theme‐based research has been implemented in the Pharmacy Department of St Vincent's Hospital (Sydney) and a body of work has been produced. To illustrate this process, our work in the area of anaphylaxis and allergy in the emergency department over 10 years is described. This model has also been implemented for other target areas with success. It is a model that could be implemented at other sites to promote a collaborative research culture in a pharmacy department and build a body of work in a targeted area.